Reviews - Sterritt, David and Beadling, Laura L. and Conterio, Martyn and Rush, Zachariah and Warne, Jude (Film International, 2013)
Abstract Jean Epstein: Critical Essays and New Translations, Sarah Keller and Jason N. Paul (eds), (2012) Amsterdam: Amsterdam University Press, 439 pp., ISBN 9789048513840 (e-bk); ISBN 9789089642929 (pbk), $49.95/£32.86 Film Genre Reader IV, Barry Keith Grant, (2012) Austin: University of Texas Press, 766 pp., ISBN 9780292742062 (pbk), $29.95; ISBN 9780292742055 (hbk), $65.00 The Romy Schneider Story Bracknelll: Reel Publishing, 141 pp., ISBN 9781905764167 (pbk), £10.00 A Social History of Iranian Cinema: Volume 4, The Globalizing Era, 1984–2010, Hamid Naficy, (2012) Durham, NC: Duke University Press, 632 pp., ISBN 9780822348788 (pbk), $29.95; ISBN 9780822348665 (hbk), $99.95 Todd Haynes, (Contemporary Film Directors), Rob White, (2013) Champaign: University of Illinois Press, 176 pp., ISBN 9780252079108 (pbk), $22.00
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9maWluLjExLjYuNzNfNQ